Long Cycling Life Supercapacitors Electrode Materials: Ultrathin Manganese Dioxide Nanoscrolls Adhered to Graphene by Electrostatic Self-Assembly. (20th August 2015) - Zhao, Kuangmin; Liu, Suqin; Wu, Yuanzhan; Lv, Kezhou; Yuan, Hao; He, Zhen
Abstract: Positively charged amine-MnO2 nanoscrolls obtained by using 3-Aminopropyltriethoxysilane (APTES) to modify hydrothermal synthesized nano-sized MnO2 scrolls, and then adhered to negatively charged reduced graphene oxides (rGO) and fabricated ultrathin MnO2 /graphene hybrids (MAG). The electrochemical behaviers of MnO2 nanoscrolls and MAG are systematically investigated by cyclic voltammetry and galvanostatic charge-discharge. As a result, a maximum specific capacitance of 326 F g −1 is achieved for the MAG with 10% of rGO (MAG-10), which is much higher than 201 F g −1 of MnO2 nanoscrolls at the current density of 0.2 A g −1 . Furthermore, all of the MAG electrodes exhibit excellent cycling performance at the current density of 2 A g −1 . In addition, contributed by the unzipping of MnO2 NSs and the restriction of curving graphene, the specific capacitance of MAG-10 electrode is slightly increased in the beginning 6000 cycles and with the capacitance retention rate of 96.24% after 10000 cycles.